De Sanctis-Cacchione Syndrome in a female infant - Case report - Amadeus Lima Rocha Caldas; Mecciene Mendes Rodrigues (Sociedade Brasileira de Dermatologia, 2013)
The De Sanctis-Cacchione Syndrome is the rarest and most severe kind of xeroderma pigmentosum, characterized by microcephaly, hypogonadism, neurological disorders, mental and growth retardation, with very few cases published. The clinical findings compatible with De Sanctis-Cacchione Syndrome and the therapeutic approach used to treat a one year and nine months old child, with previous diagnosis of xeroderma pigmentosum, are reported.